Deletion of Prkcz Increases Intermittent Ethanol Consumption in Mice. (1st August 2013) - Lee, Anna M.; Zou, Mimi E.; Lim, Jana P.; Stecher, Jackie; McMahon, Thomas; Messing, Robert O.
<x xml:space="preserve">Abstract</x> Background Prkcz has been identified as a gene whose expression is positively correlated with ethanol (EtOH) consumption in mice and is also induced by EtOH. Two proteins are produced from Prkcz: protein kinase M zeta (PKMζ), which is expressed in the nervous system and protein kinase C zeta (PKCζ), which is expressed in other tissues. We examined Prkcz−/− mice that lack PKCζ and PKMζ to investigate the role of this gene in behavioral responses to EtOH. Methods Male Prkcz−/− and wild‐type littermates were tested for EtOH consumption using 4 procedures: 24‐hour intermittent access, 4‐hour limited intermittent access, 4‐day drinking‐in‐the‐dark, and 24‐hour continuous access. We also assessed the acute hypnotic effect of EtOH, EtOH reward, and taste preference for sweet‐, bitter‐, salty‐, and umami‐flavored solutions. Finally, we determined whether EtOH could increase PKMζ and PKCζ transcripts and protein expression in wild‐type mice using quantitative PCR and Western blot analysis. Results Prkcz −/− mice consumed more EtOH than their wild‐type littermates in both intermittent access procedures, but not in the drinking‐in‐the‐dark or 24‐hour continuous access procedures. EtOH exposure increased Prkcz transcripts in cultured PC12 cells, and intermittent EtOH consumption increased PKMζ protein in the ventral striatum of wild‐type mice. Conclusions Absence of PKMζ in the brain is associated with increased EtOH intake during procedures that incorporate intermittent consumption sessions every other day. Our data suggest that EtOH induces PKMζ, which acts in a negative feedback loop to limit binge‐like EtOH consumption.